Emerging Photochemical Techniques in Green Chemistry - Neha Sahu; Rizwan Arif (International Journal of Photochemistry and Photochemical Research, 2024)
Creating environmentally friendly and sustainable chemical processes is one of the main objectives of green chemistry. A viable strategy for accomplishing this goal is the use of light to trigger chemical reactions in emerging photochemical techniques. An overview of current developments in photochemical techniques that support green chemistry is given in this abstract. Key innovations include the use of visible light photocatalysis, which offers a sustainable alternative to traditional high-energy UV light processes. Transition metal complexes, organic dyes, and semiconductor materials are highlighted as effective photocatalysts that can operate under mild conditions and with high selectivity. Furthermore, the integration of photochemical techniques with flow chemistry and continuous processing enhances reaction efficiency and scalability, reducing waste and energy consumption. Advances in photoredox catalysis have enabled the development of novel synthetic pathways, facilitating the construction of complex molecules with minimal environmental impact. The application of these techniques in natural product synthesis, pharmaceutical manufacturing, and polymer chemistry illustrates their versatility and potential for widespread industrial adoption. In conclusion, emerging photochemical techniques provide a robust platform for advancing green chemistry principles. By leveraging the energy of light, these methods offer environmentally benign alternatives to conventional chemical processes, aligning with the global imperative for sustainable development. This paper explores the recent advancements and applications of photochemical techniques in green chemistry, highlighting their potential to revolutionize synthesis processes while reducing energy consumption, waste generation, and reliance on hazardous reagents. Key areas of focus include: Solar-driven reactions: Harnessing sunlight as a clean and abundant energy source for driving chemical transformations, including photoredox catalysis and photocatalytic reactions. Solvent-free and mild conditions: Utilizing photochemistry to conduct reactions under solvent-free or mild conditions, reducing the use of volatile organic solvents and minimizing environmental footprint. Selective activation: Leveraging the selectivity of light to activate specific functional groups or bond cleavage, enabling precise control over reaction pathways and reducing the need for protecting groups
Keywords: Photochemistry; flow chemistry; green chemistry; photocatalysis; photoredox catalysis; sustainable synthesis; visible light